2013
DOI: 10.1080/00207543.2012.701777
|View full text |Cite
|
Sign up to set email alerts
|

The application of a knowledge-based reference framework to support the provision of requisite variety and customisation across collaborative networks

Abstract: The research described in this paper demonstrates how individual operational capabilities and the collective knowledge and expertise of a collaborative customer-supplier network can be harnessed to manage the challenges associated with the provision of a requisite level of product variety and customisation. It concerns the discussion and application of a previously published approach to the classification of collaborative networks, the justification of the extension to this approach and the use of the approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Lyons et al (2012) revealed how binding individual operational capabilities and collective knowledge can be used to manage the challenges of product variety across collaborative networks. Hernandez et al (2012) presented a collaborative network platform for multi-site production, where mass customisation decision-making process was facilitated in collaborative supply chain networks and collaborative dynamic decision-making for supplier selection.…”
Section: Km Knowledge Flow and Knowledge Chainmentioning
confidence: 99%
“…Lyons et al (2012) revealed how binding individual operational capabilities and collective knowledge can be used to manage the challenges of product variety across collaborative networks. Hernandez et al (2012) presented a collaborative network platform for multi-site production, where mass customisation decision-making process was facilitated in collaborative supply chain networks and collaborative dynamic decision-making for supplier selection.…”
Section: Km Knowledge Flow and Knowledge Chainmentioning
confidence: 99%
“…The next article "The Application of a Knowledge-Based Reference Framework to Support the Provision of Requisite Variety and Customisation Across Collaborative Networks", by Lyons et al (2013), concerns the discussion and application of a knowledge-based reference framework to demonstrate how product variety and customisation can be supported across different forms of collaborative customer-supplier networks. In addition, explanations are provided on how collaborative networks can be classified, how their adaptive capabilities can be established, and the characteristics and attributes that particular types of networks require in order to handle their commitment to the provision of variety and customisation.…”
mentioning
confidence: 99%
“…Thus, while modularity offers customers some level of choice, it does not offer individual customers the option to request a completely specific solution. However, true customisation allows customers to specify all key attributes of a solution (Duray et al 2000;Lyons et al 2013). Therefore, we argue that customisation in TI firms involves two dimensions: the degree of modularity and the degree of solution space freedom.…”
Section: Customisation Through Modularity and Solution Space Freedommentioning
confidence: 99%
“…First, we suggest that customisation should not be viewed one-dimensionally, i.e. as two ends of a spectrum with standardisation on one end and pure customisation on the other (see Lyons et al 2013 for an overview) but rather two-dimensionally (cf. Duray et al 2000).…”
mentioning
confidence: 99%